Blockchain privacy and scalability in a decentralized validated energy trading context with Hyperledger Fabric - Westphall, Johann (2021)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2021.